Basic Plan for the Promotion of Sports 2001-2010 (2000)
I. General: About the the significance of sport and the objective, major problems and the nature of the plan. II. Policies for the deplopment of the sports promotion measures 1. Policies for improving regional sports environments with a view to achieving lifelong participation in sport 2. Measures aimed at an overall improvement in Japan's international competitiveness 3. Measures to promote a closer link between lifelong and competitive sports and school education and school sports